An overview of Masaqid Al-Syariah on homeownership and young graduate’s wellbeing through sustainable affordable housing - Sohaimi, Nor Suzylah; Abdullah, Alias; Shuid, Syafiee; Ahmad Sarkawi, Azila (Pusat Pengajian Sains Kemasyarakatan, Universiti Sains Malaysia, 2015)
Affordable housing study in Malaysia became widespread in the early 21st century since the government encourage home ownership for all income groups and beforehand the government was focused on the low cost housing provision. However, in the early affordable housing study, most of the research emphasis on affordability among the middle income group instead of study in different generation affordability, particularly among young graduate’s affordability. Hence, this paper will discuss on young graduate housing affordability in urban area and to be more specific, observing the negative consequences of unsustainable affordable housing that reflex to young graduate’s well-being. Affordable housing issue for young graduate is a vital issue as they are considered not eligible to purchase the low cost housing and cannot afford to buy the middle and high cost house. Another essential point, young graduates who are just entering into the employment market in certain duration of the period with a monthly salary approximately RM 3000 have negative impact to their quality of life. In addition, marriage is common among fresh graduates in Malaysia and this adds to the pressure of purchasing an affordable housing that allows them to start a new family and they also consider in getting marriage and importance for them to having a house as beginning to dictate important decisions such as starting a family. Furthermore, this paper will discuss homeownership in Islamic perspective or Maqasid Syariah.